丹戎布拉大学师范教育学院汉语专业 2019 届学生对动词 “穿”、“戴”与“用”的掌握情况分析 - Felissa Tania; Ina Ina; Bun Yan Khiong (Universitas Tanjungpura, 2021)
AbstractThe three common verbs in Chinese are “chuan”, “dai” and “yong”. They have the same semantics but different specific usages. Therefore, Chinese learners often misuse these three words. In order to understand the mastery condition and analyse the difficulties of students on using the verbs of “chuan”, “dai” and